2021
DOI: 10.3390/ijms22179251
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota Features in Subjects with Down Syndrome and Periodontal Diseases: A Systematic Review

Abstract: Down syndrome (DS) is a genetic disorder associated with early-onset periodontitis and other periodontal diseases (PDs). The present work aimed to systematically review the scientific literature reporting studies in vivo on oral microbiota features in subjects with DS and related periodontal health and to highlight any correlation and difference with subjects not affected by DS, with and without PDs. PubMed, Web of Science, Scopus and Cochrane were searched for relevant studies in May 2021. The participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 82 publications
1
21
0
1
Order By: Relevance
“…Similar to our results, overuse and misuse of antibiotics in dentistry was registered in France [ 21 ], the USA [ 25 ], and the UK, where 37.6% of adults and the 39.0% of pediatric patients attending dental clinics for emergencies were administered antimicrobials and, in 57.4% of cases, antibiotics were prescribed even if no diagnosis was documented [ 31 , 32 , 33 , 34 ]. This is also consistent with findings from a cross-sectional study conducted in India, which revealed that 35% of dentists prescribed antibiotics prior to or instead of starting local treatment [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our results, overuse and misuse of antibiotics in dentistry was registered in France [ 21 ], the USA [ 25 ], and the UK, where 37.6% of adults and the 39.0% of pediatric patients attending dental clinics for emergencies were administered antimicrobials and, in 57.4% of cases, antibiotics were prescribed even if no diagnosis was documented [ 31 , 32 , 33 , 34 ]. This is also consistent with findings from a cross-sectional study conducted in India, which revealed that 35% of dentists prescribed antibiotics prior to or instead of starting local treatment [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…A similar estimate might also be computed for the progression of such diseases in periodontal subjects. Personalized prevention strategies may be even more relevant in those subjects considered at higher risk of periodontitis and peri-implantitis onset and progression, such as those suffering from comorbidities [ 4 , 10 , 14 , 15 , 30 , 33 , 78 , 79 , 80 ], especially diabetes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is a chronic inflammatory disease associated with the presence of microorganisms and sustained by host-mediated immune-inflammatory response [ 1 , 2 , 3 , 4 ], consequently establishing itself within periodontal tissues and causing their destruction with clinical attachment loss and bone loss [ 5 , 6 , 7 , 8 ] until tooth loss [ 9 ]. The inflammation of periodontal tissues, along with the dysbiotic phenomena of the periodontal microbiome [ 10 , 11 , 12 , 13 ], would also appear to play a role in the pathogenesis of systemic conditions and disorders of degenerative inflammatory and neoplastic nature [ 14 , 15 , 16 , 17 , 18 , 19 ], which, in turn, could influence the onset and, more importantly, the progression of periodontitis. The rate of progression of periodontitis is primarily estimated through both direct clinical and radiographic evidence of periodontal destruction assessed over time and indirect evidence related to biofilm accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [38] in a systematic review showed that DS patients had significantly more prevalent periodontopathogen bacteria than other mentally syndromic patients. Recent scientific evidence suggests that the presence of pathogen bacteria is necessary but not sufficient to justify the disease.…”
Section: Discussionmentioning
confidence: 99%